EKSISTENSI KOMISI YUDISIAL DALAM MEWUJUDKAN KEKUASAAN KEHAKIMAN YANG MERDEKA - Chotidjah, Nurul (Syiar Hukum, 2010)
Judicial Commission is an independent state institution created to carry out the judicial body reform. The Judicial Commission power of maintaining judgeâs dignity and behaviorÂ  is no longer exist followingÂ  the Constitutional Court Verdict No.005/PUU-IV/2006. This article examines the existence of judicial commission in the realization of independent judicial power. Theories of constitution, power separation, power distribution and independent judicial power are used to study and analyze the study. The author concludes that the objective of the creation of the Judicial Commission is to monitor and maintain the efficiency and effectiveness of judicial power.Â Â  It is recommended that the Law No.22 of 2004 onÂ  Judicial Commission be amended to enable the Judicial Commission to be able in exercising the task and power to realizeÂ  an independent judicial power following the above Constitutional Court Verdict.